Exercise‐stimulated arterial transit time in calf muscles measured by dynamic contrast‐enhanced magnetic resonance imaging. Issue 1 (15th January 2019) - Conlin, Christopher C.; Layec, Gwenael; Hanrahan, Christopher J.; Hu, Nan; Mueller, Michelle T.; Lee, Vivian S.; Zhang, Jeff L.
Abstract: The primary goal of this study was to evaluate arterial transit time (ATT) in exercise‐stimulated calf muscles as a promising indicator of muscle function. Following plantar flexion, ATT was measured by dynamic contrast‐enhanced (DCE) MRI in young and elderly healthy subjects and patients with peripheral artery disease (PAD). In the young healthy subjects, gastrocnemius ATT decreased significantly ( P  < 0.01) from 4.3 ± 1.5 to 2.4 ± 0.4 sec when exercise load increased from 4 lbs to 16 lbs. For the same load of 4 lbs, gastrocnemius ATT was lower in the elderly healthy subjects (3.2 ± 1.1 sec; P  = 0.08) and in the PAD patients (2.4 ± 1.2 sec; P  = 0.02) than in the young healthy subjects. While the sensitivity of the exercise‐stimulated ATT is diagnostically useful, it poses a challenge for arterial spin labeling (ASL), a noncontrast MRI method for measuring muscle perfusion. As a secondary goal of this study, we assessed the impact of ATT on ASL‐measured perfusion with ASL data of multiple post labeling delays (PLDs) acquired from a healthy subject. Perfusion varied substantially with PLD in the activated gastrocnemius, which can be attributed to the ATT variability as verified by a simulation. In conclusion, muscle ATT is sensitive to exercise intensity, and it potentially reflects the functional impact of aging and PAD on calf muscles. For precise measurement of exercise‐stimulated muscle perfusion, it is recommended that ATT be considered when quantifying muscle ASL data. Abstract : Magnetic resonance imaging enables accurate measurement of arterial transit time (ATT) in exercise‐stimulated calf muscles. This study aims to evaluate the potential value of exercise‐stimulated ATT in assessing muscle function. It was found that the measured ATT varied significantly between exercises of different intensities in young healthy subjects, and between different subject groups.